2015
DOI: 10.1016/j.sajb.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A survey of plants responsible for causing allergic contact dermatitis in the Amathole District, Eastern Cape, South Africa

Abstract: a b s t r a c tBackground: An inventory of allergenic plants can enable vulnerable individuals to discover the source of their dermatitis and thus prevent re-exposure. However, because of the relatively little data available in the scientific literature with regard to the adverse effects of plant, the aim of this study was to document the plants responsible for allergic contact dermatitis (ACD) in the Eastern Cape. Interview questions targeted the local names of plants that cause allergies when in direct conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In the Amathole District, Eastern Cape, South Africa, Citrus limon is utilized for diverse purposes. For instance, it is used to reduce skin itching, for skin nourishment, and the pulp left after extraction of the juice is used for the treatment of pimples and wrinkles and to soften facial skin [48]. Similar uses were also recorded in the current study whereby the participants indicated that Citrus limon is used for moisturising the skin, removing wrinkles, scars and pimples.…”
Section: Potential Of Documented Plants With High Use-valuesupporting
confidence: 57%
“…In the Amathole District, Eastern Cape, South Africa, Citrus limon is utilized for diverse purposes. For instance, it is used to reduce skin itching, for skin nourishment, and the pulp left after extraction of the juice is used for the treatment of pimples and wrinkles and to soften facial skin [48]. Similar uses were also recorded in the current study whereby the participants indicated that Citrus limon is used for moisturising the skin, removing wrinkles, scars and pimples.…”
Section: Potential Of Documented Plants With High Use-valuesupporting
confidence: 57%
“…Alexander et al (2006) furthered their research by pointing out highly significant differences in metal content between cultivars of different vegetables. Similarly, some edible species commonly grown in domestic gardens such as Allium sativum L., Mangifera indica L., Anacardium occidentale L., Daucus carota L., Lactuca sativa L. Brassica oleracea L., Carica papaya L., Musa paradisiaca L., Citrus limon (L.) Osbeck, Citrus sinensis (L.) Osbeck, Capsicum annuum L., Pastinaca sativa L., Solanum tuberosum L., and Solanum lycopersicum L. can cause allergic contact dermatitis to some people (Otang et al, 2015;Paulsen et al, 2014;Tavares et al, 2006).…”
Section: Domestic Gardensmentioning
confidence: 99%
“…The prevalence of antibiotic resistance is a continual problem due to the evolution of a potent defense mechanism against antibiotics. Therefore, it is necessary to exploit and develop novel inhibitory agents against resistant microbial pathogens (Otang and Afolayan, 2015). Plants can produce antimicrobial compounds to protect themselves from biotic attack that could be essential for microbial infection resistance.…”
Section: Introductionmentioning
confidence: 99%